Proceso de registro de inscripción del Registro de la Propiedad del Gobierno Autónomo Descentralizado del cantón Babahoyo - Estrada Hidalgo, Abelardo Danilo (2020)
The process of registration of property registration in the Decentralized Autonomous Government of the Babahoyo canton presents important shortcomings, among which the most prominent are: lack of streamlining processes, insufficient staff and absenteeism. The objective of the research work is to determine the reasons why these weaknesses occur in this public entity. The study is descriptive in which the research method used has been the inductive one, the relevant applied technique has been the survey. The results found demonstrate that in the mentioned department it is necessary to make important changes due to an improvement in the institutional image, so that the processes are optimized and the attention to the users is of quality according to the standards of the public service